İslâm Hukuku ve Pozitif Hukuk Açısından Çocukta Ceza Ehliyeti (Criminal Responsibility for Children in terms of Islamic and Positive Law) - Murat Şimşek (İnsan & Toplum)
Just as every branch of science is devoted to various aspects of human life according to its own rules and purposes, Islamic jurists have devoted themselves to the aspects of human life regarding rights and responsibilities and have considered these distinctions to be a process of physical and mental maturity. In Islamic Law, among the most hotly debated issues is in the domain of individual responsibility of which the majority of this issue relates to the child. The concept of ahliyah (license) is a qualification of a person who is competent in his understanding of legal rights and responsibilities. Ahliyah is divided into two parts: (1) the license to benefit from one’s rights (wucūb) and (2) the license to make use of one’s rights (edā). Among the questions dealt with in this issue are whether a child is competent in his understanding of criminal license, a case that deals with the age which criminal responsibility begins, what responsibilities are included, and what type of sanctions are applied. Islamic law has also adopted similar approaches as has modern positive law. In the two legal systems there are certain regulations in favor of children who have yet to attain the conscious or ability to preserve their rights. It is seen while looking at the present literature written on this matter that direct research regarding a child’s criminal ahliyah is limited to a very small amount. Taking a look at Ottoman applications of these issues, such as the Majallah and Huqūq-ı Aile Qararnāmesi, will help to shed light on the issues presented in the subject.